Housing Prices as Payment for Ecosystem Services of Urban Green Spaces: case study in Kyiv - Shyshchenko, P. G.; Havrylenko, O. P.; Tsyhanok, Ye. Yu.; Bilous, L. F. (Ukrainian Geographical Journal, 2024)
The purpose of the study is to analyze the impact of the availability of urban green spaces (UGS) and air quality on the cost of residential real estate in Kyiv. Additionally, it seeks to identify the level of awareness among city residents regarding the advantages of living close to UGSs in areas with relatively clean air and their willingness to pay a higher price for such housing. The QGIS software was used to assess pedestrian and time accessibility to recreational green spaces, and the results are depicted on the corresponding map. The least accessible for everyday recreation is the UGS in the city’s central districts, which traditionally have the highest population density and the most expensive residential real estate. The article analyzes the priority criteria for determining housing costs based on the distance from the city center and the real estate’s comfort class. The distribution of housing across different tiers and the price range of apartments in new construction in Kyiv during 2015–2021 were also examined. To identify the correlation between the cost of residential real estate in new buildings in the capital and the availability of nearby green spaces, we investigated the spatial distribution of prices across the city’s largest residential complexes. The results of spatial visualization, obtained through Voronoi diagrams or Delaunay triangulation, indicate significant disparities in housing costs between the center of Kyiv and its periphery. Logically, residential complexes with the highest apartment prices are located in the central districts of Kyiv and near the metro stations. However, most of these locations lack accessible green areas suitable for everyday recreation. Therefore, there is no positive correlation between housing prices and the presence of UGSs nearby. To achieve the research goal, we also conducted a sociological survey among Kyiv residents across the city’s various districts. The survey results indicate that most Kyiv residents do not desire, or are currently unwilling, to pay a higher price for the opportunity to live near a park or forest and breathe clean air, i.e., to enjoy the ecosystem services provided by UGSs fully. The scientific novelty of the research lies in determining the pedestrian and time accessibility of recreational green spaces in Kyiv, identifying trends in spatial clustering of the most expensive residential real estate in central city areas, and demonstrating the lack of a positive impact of the availability of green areas on the per square meter cost of housing in new developments. Additionally, the study reveals a remarkably low willingness among city residents to pay a higher price for the opportunity to access ecosystem services from available UGSs.